Menelusuri Jejak Yasuke: Analisis Perbandingan Catatan Sejarah dan Adaptasi Anime Yasuke (2021) : Tracing Yasuke's Footsteps: A Comparative Analysis of Historical Records and Anime Adaptation Yasuke (2021) - Arfianty, Rani; Sitanggang, Christopher (Undiksha Press, 2025)
This study examines the representation of Yasuke, a man of African descent who became a samurai under the rule of Oda Nobunaga in the anime Yasuke (2021), produced by Netflix and Studio MAPPA. Although the anime incorporates elements of fantasy and various narrative modifications, the historical core about Yasuke’s existence is documented in several sources, including Shinchōkōki and modern scholarly works (Lockley & Girard, 2019; Fuaddah, 2022; Rundjan, 2015). This research employs a descriptive qualitative method, with a historical approach comparing empirical data (age, background, and involvement in the Honnō-ji Incident) to the anime’s depiction. The findings indicate that, while there are similarities in the fundamental characterization, such as Yasuke’s physical traits and his relationship with Nobunaga, many additional elements, including robots, magic, and the modified account of Yasuke’s first meeting with Nobunaga, are fictional. Other notable differences emerge in the portrayal of Yasuke’s origins, the setting of his encounter with Nobunaga, and scenes following the Honnō-ji Incident. From a cultural standpoint, such adaptations can introduce Yasuke’s figure to a wide audience, although viewers seeking historical accuracy should consult period documents (such as Shinchōkōki) and modern studies. Hence, this study underscores the importance of distinguishing between historical facts and creative liberties within popular culture adaptations, so as to avoid misconceptions about Yasuke’s figure and Japanese history during Nobunaga’s era.